The Polymorphic Aggregative Phenotype of Shiga Toxin-Producing Escherichia coli O111 Depends on RpoS and Curli - Diodati, M. E. (Appl Environ Microbiol, 2016)
Escherichia coli O111 is an emerging non-O157:H7 serotype of Shiga toxin-producing E. coli (STEC). We previously reported that outbreak and environmental, but not sporadic-case, strains of STEC O111 share a distinct aggregation phenotype (M. E. Diodati, A. H. Bates, M. B. Cooley, S. Walker, R. E. Mandrell, and M. T. Brandl, Foodborne Pathog Dis 12:235−243, 2015, http://dx.doi.org/10.1089/fpd.2014.1887). We show here the natural occurrence of nonaggregative variants in single STEC O111 strains. These variants do not produce curli fimbriae and lack RpoS function but synthesize cellulose. The deletion of csgBAC or rpoS in an aggregative outbreak strain abolished aggregate formation, which was rescued when curli biogenesis or RpoS function, respectively, was restored. Complementation of a nonaggregative variant with RpoS also conferred curli production and aggregation. These observations were supported by Western blotting with an anti-CsgA antibody. Immunomicroscopy revealed that curli were undetectable on the cells of the nonaggregative variant and the RpoS mutant but were present in large quantities in the intercellular matrix of the assemblages formed by aggregative strains. Sequence analysis of rpoS in the aggregative strain and its variant showed a single substitution of threonine for asparagine at amino acid 124. Our results indicate that the multicellular behavior of STEC O111 is RpoS dependent via positive regulation of curli production. Aggregation may confer a fitness advantage in O111 outbreak strains under stressful conditions in hydrodynamic environments along the food production chain and in the host, while the occurrence of nonaggregative variants may allow the cell population to adapt to conditions benefiting a planktonic lifestyle.